THE EVOLUTION OF PHILOSOPHICAL VIEWS ON THE SPIRITUAL PERFECTION OF THE INDIVIDUAL IN THE WORKS OF EASTERN THINKERS (Scientific journal of the Fergana State University, 2024)
The article describes the views of Eastern thinkers on education, methods and means of achieving spiritual perfection of the individual, especially on all-round development of young people, raising their spiritual, moral and intellectual potential in accordance with world standards. The content of the works of Imam Bukhari, Farabi, Ibn Sina, Abu Hamid Ghazali, Navai, Koshifi, A. Avloni dedicated to spiritual and moral education is described.